Is Noncardiac Chest Pain Truly Noncardiac?. Issue 14 (June 2020) - Teragawa, Hiroki; Oshita, Chikage; Orita, Yuichi
Many causes of noncardiac chest pain (NCCP) have been studied and gastroesophageal reflux disease is considered to be the major cause. However, studies have reported that treatment with a proton pump inhibitor does not effectively provide relief for NCCP-related symptoms, and these symptoms frequently recur. These findings suggest that patients with cardiac disease may be excluded completely from the NCCP group. Several examinations can be conducted to verify the presence of cardiac disease. Such examinations include the assessment of biochemical markers, rest and exercise electrocardiogram, echocardiography, cardiac computed tomography, stress myocardial perfusion imaging, cardiac magnetic resonance imaging, and coronary angiography (CAG). However, the presence of functional coronary artery diseases (CADs), such as vasospastic angina and/or microvascular angina, cannot be detected using these modalities. These functional CADs can be diagnosed by CAG with spasm-provocation testing and/or physiological coronary measurement. Thus, when a patient who is suspected of having NCCP takes a proton pump inhibitor and does not respond well, further examination—including assessment for possible functional CADs—may be needed.